Recent advances based on Mg anodes and their interfacial modulation in Mg batteries - Fanfan Liu; Guoqin Cao; Jinjin Ban; Honghong Lei; Yan Zhang; Guosheng Shao; Aiguo Zhou; Li zhen Fan; Junhua Hu (Journal of Magnesium and Alloys, 2022)
Magnesium (Mg) batteries (MBs), as post-lithium-ion batteries, have received great attention in recent years due to their advantages of high energy density, low cost, and safety insurance. However, the formation of passivation layers on the surface of Mg metal anode and the poor compatibility between Mg metal and conventional electrolytes during charge-discharge cycles seriously affect the performance of MBs. The great possibility of generating Mg dendrites has also caused controversy among researchers. Moreover, the regulation of Mg deposition and the enhancement of battery cycle stability is largely limited by interfacial stability between Mg metal anode and electrolyte. In this review, recent advances in interfacial science and engineering of MBs are summarized and discussed. Special attention is given to interfacial chemistry including passivation layer formation, incompatibilities, ion transport, and dendrite growth. Strategies for building stable electrode/interfaces, such as anode designing and electrolyte modification, construction of artificial solid electrolyte interphase (SEI) layers, and development of solid-state electrolytes to improve interfacial contacts and inhibit Mg dendrite and passivation layer formation, are reviewed. Innovative approaches, representative examples, and challenges in developing high-performance anodes are described in detail. Based on the review of these strategies, reference is provided for future research to improve the performance of MBs, especially in terms of interface and anode design.